Seasonal Ground Surface Change Detected by DInSAR at Cape Bounty, Melville Island, Nunavut - Robson, Greg (2020)
Differential interferometry of synthetic aperture radar (DInSAR) analysis can be used to generate high-precision surface displacement maps in continuous permafrost environments, capturing isotropic surface subsidence and uplift associated with the seasonal freeze and thaw cycle. We generated seasonal displacement maps using DInSAR with ultrafine-beam Radarsat-2 images for summers 2013, 2015 and 2019 at Cape Bounty, Melville Island, and examined them in combination with a land cover classification, meteorological data, topographic data, optical satellite imagery, and in situ measures of soil moisture, soil temperature and active layer thickness. Displacement magnitudes (estimated uncertainty ± 1 cm) of up to 10 cm per 48-day DInSAR stack were detected, but the vast majority of change was far smaller (up to 4 cm). Significant surface displacement was found to be most extensive and of the greatest magnitude in select low-lying, wet, and sloping areas. We speculate that precipitation may be the most important control on the extent of seasonal frost heave, as 2019 showed higher levels of surface displacement than 2013. Despite both summers having similar thawing degree days, 2019 had double the cumulative rainfall by mid-August. Areas which showed significant displacement in multiple years were sparse but densely clustered in wet, low lying areas, on steep slopes or ridges, or close to the coast. Cumulative displacement across all three years was also examined: areas with large cumulative uplift were constrained to upland areas, and conversely areas showing large cumulative subsidence were constrained to low-lying areas; this may be due to contrasting ground ice concentrations and water availability associated with different sediment composition and frost susceptibility above and below the local marine limit (estimated at 70 m a.s.l.). DInSAR also captured the expansion of two medium-sized retrogressive thaw slumps (RTS), appearing to successfully map accumulation of slumped material at the foot of the RTS headwalls, ...